O professor é um profissional? ‘Verdades’ da Grécia Clássica e de dicionários brasileiros de Língua Portuguesa. - Medeiros, Rosa Maria da Silva (2015)
In this thesis, we reflect about what form of rationality we are dealing with by consulting meanings about the teacher in Brazilian dictionaries of Portuguese language. Do we come across a form of rationality that represents the teacher as a Professional or just as a performer? We aim at analyzing what identity profiles of teachers are made by Brazilian dictionary rationality of Portuguese language from 19th to 21st centuries, to the investigation of what wishes of truth about the teacher can remote to Classic Greece; and discuss effects of truth about the teacher that rule, unify and attach us to a specific identity profile and social environment. Allying a historic study about the teacher from Classic Greece philosophers’ speeches and from the analysis of a Brazilian dictionary rationality of Portuguese language, our way of interpretation is oriented by Foucauldian theories (2013, 2012, 2009, 2003, 2000, 1994); by Aranha’s academic studies (2006a, 2006b); Zeifert (2004) related to the History and Philosophy of Greek Education; by Orlandi (2002) related to Discursive Lexicography; by Tardif’s orientation (2009, 2010, 2011), Behrens (1999, 2007), Libâneo & Pimenta (1999), Nóvoa (1995, 1999), Pollak (1992) etc. Teacher’s identification, in Classic Greece, with the meritorious effect in not being Professional; and in dictionary rationality with the predominant effect of performer, signals a social memory where it prevails the teacher’s identity as being technical, performer, resigned to financial expectations and scarcely Professional. Most of the wishes of truth about teacher, built by dictionaries from 19th to 21st centuries, are governed by a technical rationality of conservative paradigm itself. Those wishes of truth meet the power of teacher’s marginalization, since by excluding him/her from the order of the profession and the Professional, the teacher’s disempowerment from the social environment is activated and put into circulation. Resisting to such will of truth demands from the Teacher the rethinking on the roles on social formation and, especially, the rethinking on themselves. The Teacher can challenge and resist the structures of domination that bind and attach to a technician identification, social and economically devalued and renegade by future generations. Whishes of thruth about the Teacher constructed in Classic Greece and in Brazilian dictionary rationality make imperative a work of the Teacher’s memory rearrangement. An investment in political terms, in coherence, unit and identity teacher’s terms for division of new identity profile of Professional Teacher’s order to occur on heterogeneous ground of memory. Resisting to reductionism of being identified as ‘the one who teaches’, assuming the identification of a certified Professional in licentiate course that enables him/her planning, teaching knowledge, giving classes, developing material and evaluating teaching/learning process in different teaching contexts and levels of education. The engagement for the identity and Professional valorization is necessary to attach Professional Teacher’s history and memory in such way that this same memory works for itself and inspires the Teacher’s collectivity and future generations